Pembangunan Infrastruktur di Desa Saentis Kecamatan Percut Sei Tuan Kabupaten Deli Serdang - Gracia Feby Yeski Sitepu; Hanna Teresia Sidabutar; Ikhsanul Fadly; Julia Ivanna (Journal on Education, 2024)
The implementation of road infrastructure development is very important to be realized and is the most basic means that aims to support the smoothness, distribution of goods, and human transportation networks. Community welfare can be seen from the physical condition of an area about the facilities provided by the government. This research uses the literature study method, which means that this research is carried out by collecting, evaluating, and analyzing information from various library sources, such as books, journals, articles, and other documents. The process begins with identifying the topic or research question you want answered. Then, researchers conduct literature searches using databases, libraries, or other electronic sources to find relevant sources. Once relevant sources are identified, researchers carefully and critically read each source to understand its contents Information that.